Analysis on advantages and disadvantages of technology used by Chinese men`s basketball team in the basketball match at the 29th Olympic Games - Xu, Y.; Chen, Z. (International Journal of Sports Science and Engineering, 2009)
This article makes a statistics of 13 skill indexes of Chinese Men`s basketball matches in 29th Olympic Games according to the evaluation standard of International Basketball Association` skill index. Grey relational analysis theory is used to make a quantitative analysis of the skill indexes according to the statistical data. The result shows the defense skill is superior to attack skill. This research achievement supplies theoretical reference for the scientific training of Chinese men`s basketball team